The Implications of Repealing The Law of Mandatory Company Registration on The Company Legality After The Enaction of Indonesia’s Job Creation Law - Ronal Agusmi; Husni Husni; Muhammad Gaussyah; Putri Julia Mizulni (Universitas Islam Negeri Antasari Banjarmasin, 2022)
Abstract: The legality of a company, an enterprise, or a business entity is compulsory to be accomplished before the establishment. The legality is represented by the company registration. This research aims to explore and analyze the legality, analyze the legal consequence, and describe the registration procedures for a company that has been registered after the Law of Mandatory Company Registration was repealed. The method of this research is normative legal research using the statute approach and conceptual approach. As the results of this study, it is found that a company registered after the repealing of the Mandatory Company Registration Law is still legal for the law. However, the company should reregister to obtain the maximum benefits from the country. A Limited Partnership (Commanditaire Vennootschap), General Partnership, and Limited Liability Partnership (Matschaap) that have been registered in the district court after the repealing of the Mandatory Company Registration Law must be reregistered through an enterprise management system by using an online single submission (OSS). The regulations in the Law of Mandatory Company Registration and other related regulations are no longer valid according to the regulations in Job Creation Law Article 116 chapter VI section 9Keywords: Implications; Mandatory Company Registration; Job Creation Abstrak: Legalitas badan usaha merupakan hal yang wajib dipenuhi sebelum mendirikan usaha. Legalitas tersebut tercermin dengan di daftarkannya badan usaha. Penelitian bertujuan untuk untuk mengkaji dan menganalisis legalitas hukum, menganalisis konsekuensi hukum yang timbul, serta untuk mengkaji dan menjelaskan mekanisme pendaftaran perusahaan yang telah terdaftar pasca pencabutan UUWDP. Jenis penelitian yang digunakan adalah yuridis normatif, pendekatan yang digunakan dalam penelitian ini adalah pendekatan perundang-undangan (statute approach) dan pendekatan konsep (conceptual approach). Hasil penelitian dapat di jelaskan bahwa perusahaan yang telah terdaftar setelah UUWD dicabut oleh UUCK, perusahaan tersebut tetap legal dimata hukum. Akan tetapi idealnya perusahaan tersebut di daftarkan ulang untuk memperoleh manfaat yang maksimal dari Negara. Perusahaan yang berbentuk persekutuan komanditer, persekutuan firma dan persekutuan perdata yang telah terdaftar di pengadilan negeri setelah UUWDP dicabut harus melakukan pendaftaran ulang melalui sistem administrasi badan usaha dengan mengimplementasikan online single subsmission. Regulasi undang-undang wajib daftar perusahaan dan aturan turunannya tidak berlaku lagi sesuai dengan ketentuan Pasal 116 bab VI bagian kesembilan UUCK.Kata kunci: Implikasi; Wajib Daftar Perusahan; Cipta Kerja